Anti-aging anticorrosive coating material for marine equipment and preparation method thereof

CN122917682APending Publication Date: 2026-10-16SHANGHAI FENGCHANG SHIPPING ENG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611268828.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-20
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0006]发明目的:本发明旨在提供一种海洋装备用抗老化防腐涂层材料及其制备方法,以解决现有海洋装备防腐涂层易老化、开裂及脱落,且难以兼顾附着力、柔韧性、刚性、耐冲击性、耐腐蚀性和耐磨性的问题,提高涂层的耐盐雾及长期防护性能,延长海洋装备的服役寿命

Benefits of technology

[0051] This invention employs a carbon-titanium cage resin/vinyl ester resin composite matrix. The inorganic structures of titanium and silicon in the carbon-titanium cage resin synergistically enhance the coating matrix's resistance to corrosion and structural stability. Surface modification of chopped glass fibers using a silane coupling agent strengthens the interfacial bonding between the glass fibers and the resin matrix, improving the coating's impact resistance, wear resistance, and crack resistance. Furthermore, modification of dendritic porous graphene using a silane coupling agent improves the graphene's dispersibility and interfacial bonding within the resin matrix. Its layered and porous structure acts as a barrier against corrosive media, thereby enhancing the coating's corrosion resistance and anti-aging properties.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application relates to the technical field of marine coating, and particularly relates to an anti-aging anticorrosive coating material for marine equipment and a preparation method thereof. The coating material comprises, by weight, 100 parts of carbon titanium cage resin / vinyl ester resin composite matrix, 1.0-2.5 parts of silane coupling agent modified glass fiber, 0.1-2.0 parts of silane coupling agent modified graphene and 0.1-10 parts of additives. By compounding carbon titanium cage resin and vinyl ester resin, and introducing silane coupling agent modified glass fiber and dendritic porous graphene, a multi-scale synergistic reinforcing and corrosion medium barrier structure is formed, the interface bonding and structural stability of the coating are improved, the adhesion, impact resistance, wear resistance, acid and alkali corrosion resistance and salt spray resistance of the coating are improved, and the aging, cracking and peeling of the coating are delayed, so that the coating is suitable for long-term protection of the metal surface of marine equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of marine coatings technology, and in particular to an anti-aging and anti-corrosion coating material for marine equipment and its preparation method. Background Technology

[0002] Marine equipment operates in complex environments characterized by high humidity, high salinity, high UV radiation, and fluctuating temperatures. Metal components, particularly those on ship decks such as pipes, flanges, hydraulic lines, cables, and cargo oil lines, are particularly susceptible to corrosion due to the combined effects of seawater salt spray, humid air, and mechanical impact and friction. Applying anti-corrosion coatings is currently a crucial technique for delaying corrosion and extending the service life of marine equipment. However, existing anti-corrosion coatings for marine equipment are prone to aging, cracking, blistering, powdering, and peeling during long-term service. This allows corrosive media to gradually penetrate the metal substrate, reducing the coating's anti-corrosion performance and potentially leading to equipment corrosion, leaks, and increased maintenance costs.

[0003] Existing anti-corrosion coatings typically use organic resins such as epoxy resin, polyurethane, and vinyl ester resin as the main film-forming materials. While some high-hardness resin systems exhibit good corrosion resistance and abrasion resistance, the cured coatings have high rigidity and low elongation at break. When ship equipment deforms due to temperature changes, pressure variations, or mechanical vibrations, the coating is prone to stress concentration and cracking. On the other hand, while more flexible coatings can adapt to a certain degree of substrate deformation, their impact resistance, abrasion resistance, and long-term corrosion resistance are easily compromised. Therefore, existing coatings struggle to simultaneously achieve good adhesion, flexibility, rigidity, impact resistance, abrasion resistance, and long-term corrosion resistance.

[0004] Furthermore, salt spray in marine environments has a strong penetrating effect. Once microcracks or localized defects form in the coating, moisture and chloride ions can easily penetrate along the interior of the coating or the interface between the coating and the metal substrate, thus accelerating coating failure. Existing coating reinforcement methods often struggle to simultaneously address the interfacial bonding between the reinforcing material and the resin matrix, as well as the overall flexibility of the coating. Uneven dispersion of the reinforcing material can also lead to localized defects, further affecting the coating's corrosion resistance and aging resistance.

[0005] Therefore, there is an urgent need to develop an anti-aging and anti-corrosion coating material suitable for marine equipment, which can improve the adhesion between the coating and the metal substrate, achieve a balance between rigidity and flexibility, and further improve the coating's resistance to salt spray, impact, corrosion and wear, thereby extending the service life of the anti-corrosion coating for marine equipment. Summary of the Invention

[0006] Purpose of the invention: The present invention aims to provide an anti-aging and anti-corrosion coating material for marine equipment and its preparation method, so as to solve the problems of existing anti-corrosion coatings for marine equipment being prone to aging, cracking and peeling, and having difficulty in simultaneously achieving adhesion, flexibility, rigidity, impact resistance, corrosion resistance and wear resistance, thereby improving the coating's salt spray resistance and long-term protective performance, and extending the service life of marine equipment.

[0007] The technical solution of the present invention:

[0008] This invention employs a composite matrix constructed from carbon-titanium cage resin and vinyl ester resin. Utilizing the synergistic effect between the inorganic structure of the carbon-titanium cage resin and the organic structure of the vinyl ester resin, the overall structural stability and corrosion resistance of the coating are improved while maintaining the good film-forming properties and media resistance of the vinyl ester resin. The composite of carbon-titanium cage resin and vinyl ester resin forms a continuous resin phase with good interfacial bonding, reducing the possibility of internal coating defects and rapid penetration of corrosive media along the resin interior. This enhances the coating's resistance to acid, alkali, and salt spray environments and helps delay coating aging and failure during long-term service.

[0009] This invention further employs a silane coupling agent to modify the surface of chopped glass fibers. The silane coupling agent can form a reactive or interfacial structure on the glass fiber surface, improving the interfacial bonding between the glass fiber and the resin matrix, allowing the glass fiber to be more stably dispersed and embedded in the resin matrix. When the coating is subjected to impact, friction, or external stress, the glass fiber can bear and transfer part of the external load, reducing local stress concentration and inhibiting crack propagation. Therefore, it can improve the impact resistance, abrasion resistance, and crack resistance of the coating, and help maintain the overall integrity of the coating.

[0010] This invention utilizes dendritic porous graphene modified with a silane coupling agent. On one hand, the silane coupling agent improves the interfacial compatibility and dispersion stability between graphene and the resin matrix, reducing the possibility of graphene agglomeration and defect formation. On the other hand, graphene itself has a layered structure, which can form relatively tortuous diffusion paths for corrosive media within the coating, extending the migration paths of corrosive media such as moisture, oxygen, and chloride ions to the metal substrate. Simultaneously, the dendritic porous structure further increases the contact interface between graphene and the resin matrix, enabling the formation of a more uniform microscopic barrier structure within the coating, thereby improving the coating's corrosion resistance and anti-aging properties.

[0011] Glass fiber and modified graphene form a multi-scale reinforcement structure combining micron and nanoscale in the coating. Glass fiber primarily undertakes macroscopic load transfer and crack propagation inhibition, while modified graphene mainly functions as a microscopic barrier, interface reinforcement, and defect filling. Their synergistic effect across different scales enables the coating to simultaneously achieve good mechanical properties and shielding protection. Therefore, this invention does not rely on a single reinforcing component to improve a particular property, but rather achieves a good comprehensive balance between adhesion, impact resistance, abrasion resistance, acid and alkali corrosion resistance, and salt spray resistance through a multi-level synergistic structure of "carbon-titanium cage resin / vinyl ester resin composite matrix—modified glass fiber—modified graphene".

[0012] In a first aspect, the present invention provides an anti-aging and anti-corrosion coating material for marine equipment, wherein the coating material comprises the following components in parts by weight:

[0013] 100 parts of carbon-titanium cage resin / vinyl ester resin composite matrix;

[0014] 1.0~2.5 parts of silane coupling agent modified glass fiber;

[0015] 0.1-2.0 parts of graphene modified with silane coupling agent;

[0016] Additives: 0.1-10 parts.

[0017] In some embodiments, the coating material, by weight, comprises the following components:

[0018] 100 parts of carbon-titanium cage resin / vinyl ester resin composite matrix;

[0019] 1.0~1.6 parts of silane coupling agent modified glass fiber;

[0020] 0.1~0.35 parts of graphene modified with silane coupling agent;

[0021] Additives: 0.1-10 parts.

[0022] In some embodiments, the method for preparing the carbon-titanium cage modified vinyl ester resin includes the following steps:

[0023] S1. Pretreatment of vinyl ester resin: Add vinyl ester resin to a reaction vessel equipped with a mechanical stirrer, thermometer and cooling device, and stir thoroughly until homogeneous; the stirring temperature is 25-35℃, the stirring rate is 300-500 r / min, and the stirring time is 10-20 min.

[0024] S2. Adding carbon-titanium cage resin 1020: Under continuous stirring, slowly add carbon-titanium cage resin 1020 to the vinyl ester resin. The addition time is 10-30 min; the stirring speed is 500-800 r / min; the stirring temperature is 25-40℃; after the addition is complete, continue stirring for 20-40 min.

[0025] S3. High-speed dispersion: Increase the stirring speed to 1000-1800 r / min for dispersion, and the dispersion time is 20-40 min; high-speed shearing is used to make the carbon titanium cage resin form a uniform dispersion in the vinyl ester resin.

[0026] S4. Adding additives: Add the dispersant and defoamer to the above system; stir at a speed of 500-800 r / min for 10-20 min to uniformly disperse the dispersant and defoamer, and obtain a mixed resin system;

[0027] S5. Vacuum degassing: The mixed resin system is subjected to vacuum degassing treatment at a vacuum degree of -0.06 to -0.09 MPa for a treatment time of 5 to 15 min to obtain a carbon-titanium cage resin / vinyl ester resin composite matrix.

[0028] Further, calculated by mass parts, the ratio of the added carbon-titanium cage resin 1020: vinyl ester resin: dispersant: defoamer is 50-70 parts: 30-50 parts: 0.1-0.5 parts: 0.05-0.3 parts. Even further, the ratio of the added carbon-titanium cage resin 1020: vinyl ester resin: dispersant: defoamer is 60 parts: 40 parts: 0.5 parts: 0.2 parts.

[0029] In some embodiments, the vinyl ester resin is selected from one or more combinations of bisphenol A type epoxy vinyl ester resin, phenolic type epoxy vinyl ester resin, or polyurethane modified vinyl ester resin. Further, the vinyl ester resin is a bisphenol A type epoxy vinyl ester resin. For example, one or more combinations of commercially available products such as AOC ATLAC® 430, ATLAC 430 ACT, ATLAC 430 LV GT250, and DREAKANE™ 411 can be selected.

[0030] In some embodiments, the dispersant and defoamer can be commercially available conventional products. For example, the dispersant is selected from one or more of polycarboxylic acid dispersants, polyurethane dispersants, and block copolymer dispersants; the defoamer is selected from one or more of silicone defoamers, polyether defoamers, and mineral oil defoamers.

[0031] In some embodiments, the silane coupling agent is selected from one or a combination of two of KH-550 and / or KH-560.

[0032] In some embodiments, the glass fiber is chopped glass fiber, such as Megastone Glass 410, with a length of 3-12 mm and a single filament diameter of 9-13 μm.

[0033] In some embodiments, the preparation method of the silane coupling agent modified glass fiber includes the following steps:

[0034] S1: After heating and drying the glass fiber, cool it to room temperature;

[0035] S2: Mix silane coupling agent, water and ethanol to prepare a treatment solution, adjust the pH to 4-5 and stir;

[0036] S3: The glass fiber treated in S1 is added to the above treatment solution for immersion. After immersion, it is filtered and dried to obtain silane coupling agent modified glass fiber.

[0037] Furthermore, the heating and drying temperature described in S1 is 80–100°C, and the drying time is 1–2 h.

[0038] Furthermore, the mass ratio of the silane coupling agent, water, and ethanol is 1 part: 4 parts: 95 parts.

[0039] Furthermore, the mass ratio of the glass fiber to the treatment liquid is 1:10~20.

[0040] In some embodiments, the graphene is dendritic porous graphene.

[0041] In some embodiments, the preparation method of the silane coupling agent modified graphene includes the following steps:

[0042] S1: Mix silane coupling agent, water and ethanol to prepare a treatment solution, adjust the pH to 4-5 and stir;

[0043] S2: First, add graphene to ethanol and stir at low speed until homogeneous to obtain a graphene dispersion;

[0044] S3: Add the graphene dispersion to the treatment solution and mix. Stir and treat. After treatment, centrifuge, wash and vacuum dry to obtain silane coupling agent modified graphene.

[0045] In some embodiments, the additives include, but are not limited to, one or more of dispersants, defoamers, thixotropic agents, anti-aging agents, curing agents, and accelerators.

[0046] In a second aspect, the present invention provides a method for preparing the above-mentioned anti-aging and anti-corrosion coating material for marine equipment, specifically including the following steps:

[0047] The silane coupling agent-modified graphene is added to the carbon-titanium cage resin / vinyl ester resin composite matrix and dispersed uniformly at high speed; then the silane coupling agent-modified glass fiber is added and stirred evenly; the additives are added further, and after mixing evenly, vacuum degassing is performed to obtain the anti-aging and anti-corrosion coating material for marine equipment.

[0048] In some embodiments, the high-speed dispersion is performed at a rotation speed of 800–1500 r / min for a duration of 20–40 min.

[0049] In some embodiments, the vacuum degree of the vacuum degassing treatment is -0.06 to -0.09 MPa, the degassing time is 5 to 15 minutes, and the degassing temperature is 25 to 40°C.

[0050] Beneficial effects:

[0051] This invention employs a carbon-titanium cage resin / vinyl ester resin composite matrix. The inorganic structures of titanium and silicon in the carbon-titanium cage resin synergistically enhance the coating matrix's resistance to corrosion and structural stability. Surface modification of chopped glass fibers using a silane coupling agent strengthens the interfacial bonding between the glass fibers and the resin matrix, improving the coating's impact resistance, wear resistance, and crack resistance. Furthermore, modification of dendritic porous graphene using a silane coupling agent improves the graphene's dispersibility and interfacial bonding within the resin matrix. Its layered and porous structure acts as a barrier against corrosive media, thereby enhancing the coating's corrosion resistance and anti-aging properties.

[0052] Meanwhile, the glass fiber and graphene form a synergistic reinforcement system at the micron and nanoscale, giving the coating both high rigidity and flexibility. Therefore, this invention, by compounding carbon-titanium cage resin with a specific vinyl ester resin and then combining it with specifically interface-modified glass fiber and graphene, can obtain a marine anti-corrosion coating that combines rigidity, flexibility, impact resistance, and long-term salt spray resistance, suitable for long-term protection of marine equipment surfaces. Detailed Implementation

[0053] The present invention will be described below with reference to specific embodiments. It should be noted that the following embodiments are examples of the present invention and are used only to illustrate the invention, not to limit it. Other combinations and various modifications within the scope of the present invention can be made without departing from its spirit or scope.

[0054] Unless otherwise specified, all chemical reagents used in this invention are commercially available analytical grade. The glass fiber is chopped megalithic glass fiber 410, with a length of 3-12 mm and a single filament diameter of 9-13 μm. The graphene was purchased from Hunan Runzhong New Material Technology Co., Ltd., and is a dendritic porous graphene with 3-5 layers, a sheet size of 1-10 μm, and a sheet thickness of 1.5-1.8 nm.

[0055] Example 1

[0056] This embodiment provides an anti-corrosion coating. Calculated by mass parts, the raw materials of the coating include 100 parts of carbon-titanium cage resin / vinyl ester resin composite matrix, 1.5 parts of KH-560 modified glass fiber, 0.25 parts of KH-560 modified graphene, 0.2 parts of defoamer (tributyl phosphate), and 0.5 parts of dispersant (BYK-110).

[0057] The preparation method of the anti-corrosion coating material includes: adding the KH-560 modified graphene to the carbon-titanium cage resin / vinyl ester resin composite matrix, and dispersing it at high speed for 30 min at 800 r / min until uniformly dispersed; then adding the KH-560 modified glass fiber and stirring at 300 r / min for 20 min; continuing to add the additives, mixing at 400 r / min for 30 min until uniformly stirred, and then performing vacuum degassing treatment to obtain the anti-aging and anti-corrosion coating material for marine equipment.

[0058] The preparation method of the carbon-titanium cage resin / vinyl ester resin composite matrix is ​​as follows:

[0059] S1. By weight, add 40 parts of vinyl ester resin (AOC ATLAC® 430) to a reaction vessel equipped with a mechanical stirrer, thermometer and cooling device, and stir at 300 rpm for 20 min at 30°C;

[0060] S2. Under continuous stirring, 60 parts of 1020 carbon titanium cage resin (Shanghai Qixiang Qingchen) were slowly added to the vinyl ester resin at 500 r / min. After the addition was completed, stirring was continued for 30 min.

[0061] S3. Increase the stirring speed to 1000–1800 r / min for dispersion, and the dispersion time is 20–40 min. High-speed shearing is used to achieve a uniform dispersion of the carbon-titanium cage resin in the vinyl ester resin.

[0062] S4. Then, 0.5 parts of dispersant (BYK-110) and 0.3 parts of defoamer (tributyl phosphate) were added to the above system and stirred at 500 r / min for 30 min to obtain a mixed resin system.

[0063] S5. The mixed resin system is subjected to vacuum degassing treatment at a vacuum degree of -0.08 MPa for 10 min to obtain a carbon-titanium cage resin / vinyl ester resin composite matrix.

[0064] The preparation method of KH-560 modified glass fiber is as follows:

[0065] S1: Heat and dry the glass fiber at 100℃ for 2 hours, then cool it to room temperature;

[0066] S2: By mass, mix 1 part of silane coupling agent KH-560, 4 parts of deionized water and 95 parts of ethanol to prepare a treatment solution, adjust the pH to 4 with acetic acid, and stir at room temperature for 30 minutes.

[0067] S3: Add 10g of glass fiber treated in S1 to 150g of the above treatment solution, stir and soak at 200r / min for 30min, filter after soaking and dry at 70℃ for 2h, then heat to 100℃ for 1h to obtain silane coupling agent modified glass fiber.

[0068] The preparation method of KH-560 modified graphene is as follows:

[0069] S1: By mass, mix 2 parts of silane coupling agent KH-560, 49 parts of water and 49 parts of ethanol to prepare a treatment solution, adjust the pH to 4 with acetic acid, and stir at room temperature for 30 minutes.

[0070] S2: First, add 10g of graphene to 200g of ethanol and stir at 200r / min until homogeneous to obtain a graphene dispersion.

[0071] S3: Add 200g of the above graphene dispersion to 50g of the treatment solution and mix. Stir and treat. After treatment, centrifuge, wash and vacuum dry to obtain silane coupling agent modified graphene.

[0072] Example 2

[0073] This embodiment provides a coating material. Calculated by mass parts, the raw materials of the coating include 100 parts of carbon-titanium cage resin / vinyl ester resin composite matrix, 1 part of KH-560 modified glass fiber, 0.1 parts of KH-560 modified graphene, 0.2 parts of defoamer, and 0.5 parts of dispersant.

[0074] This embodiment provides a method for preparing the coating material, which is the same as in Embodiment 1.

[0075] Example 3

[0076] This embodiment provides a coating material. Calculated by mass parts, the raw materials of the coating include 100 parts of carbon-titanium cage resin / vinyl ester resin composite matrix, 2.5 parts of KH-560 modified glass fiber, 0.25 parts of KH-560 modified graphene, 0.2 parts of defoamer, and 0.5 parts of dispersant.

[0077] This embodiment provides a method for preparing the coating material, which is the same as in Embodiment 1.

[0078] Example 4

[0079] This embodiment provides a coating material. Calculated by mass parts, the raw materials of the coating include 100 parts of carbon-titanium cage resin / vinyl ester resin composite matrix, 1.5 parts of KH-560 modified glass fiber, 2.0 parts of KH-560 modified graphene, 0.2 parts of defoamer, and 0.5 parts of dispersant.

[0080] This embodiment provides a method for preparing the coating material, which is the same as in Embodiment 1.

[0081] Comparative Example 1

[0082] This comparative example provides a coating material, which, by mass parts, comprises 100 parts vinyl ester resin, 1.5 parts KH-560 modified glass fiber, 0.25 parts KH-560 modified graphene, 0.2 parts defoamer, and 0.5 parts dispersant.

[0083] This embodiment provides a method for preparing the coating material, which is the same as in Example 1, except that a vinyl ester resin is used instead of the carbon-titanium cage resin / vinyl ester resin composite matrix.

[0084] Comparative Example 2

[0085] This comparative example provides a coating material, which, by mass parts, comprises 100 parts of carbon-titanium cage resin / vinyl ester resin composite matrix, 1.5 parts of chopped giant stone glass fiber 410, 0.25 parts of KH-560 modified graphene, 0.2 parts of defoamer, and 0.5 parts of dispersant.

[0086] This embodiment provides a method for preparing the coating material, which is the same as in Embodiment 1, except that short-cut boulder glass fiber 410 is used instead of KH-560 modified glass fiber.

[0087] Comparative Example 3

[0088] This comparative example provides a coating material, which, by mass parts, comprises 100 parts of carbon-titanium cage resin / vinyl ester resin composite matrix, 1.5 parts of KH-560 modified glass fiber, 0.25 parts of graphene, 0.2 parts of defoamer, and 0.5 parts of dispersant.

[0089] This embodiment provides a method for preparing the coating material, which is the same as in Example 1, except that graphene is used instead of KH-560 modified graphene.

[0090] Comparative Example 4

[0091] This comparative example provides a coating material, which, by mass parts, comprises 100 parts of vinyl ester resin composite matrix, 1.5 parts of chopped boulders glass fiber 410, 0.25 parts of graphene, 0.2 parts of defoamer, and 0.5 parts of dispersant.

[0092] This embodiment provides a method for preparing the coating material, which is the same as in Example 1, except that vinyl ester resin is used to replace the carbon-titanium cage resin / vinyl ester resin composite matrix, short-cut megalithic glass fiber 410 is used to replace KH-560 modified glass fiber, and graphene is used to replace KH-560 modified graphene.

[0093] Comparative Example 5

[0094] This embodiment provides a coating material. Calculated by mass parts, the raw materials of the coating include 100 parts of carbon-titanium cage resin / epoxy resin composite matrix, 1.5 parts of KH-560 modified glass fiber, 0.25 parts of KH-560 modified graphene, 0.2 parts of defoamer (tributyl phosphate), and 0.5 parts of dispersant (BYK-110).

[0095] The preparation method of the carbon-titanium cage resin / epoxy resin composite matrix is ​​as follows:

[0096] S1. By mass, add 40 parts of epoxy resin (bisphenol A type vinyl ester resin WEST SYSTEM 105) to a reaction vessel equipped with a mechanical stirrer, thermometer and cooling device, and stir at 300 rpm for 20 min at 30°C.

[0097] S2. Under continuous stirring, 60 parts of 1020 carbon titanium cage resin (Shanghai Qixiang Qingchen) were slowly added to the epoxy resin at 500 r / min. After the addition was completed, stirring was continued for 30 min.

[0098] S3. Increase the stirring speed to 1000-1800 r / min for dispersion, and disperse for 20-40 min. High-speed shearing ensures that the carbon-titanium cage resin is uniformly dispersed in the epoxy resin.

[0099] S4. Then, 0.5 parts of dispersant (BYK-110) and 0.3 parts of defoamer (tributyl phosphate) were added to the above system and stirred at 500 r / min for 30 min to obtain a mixed resin system.

[0100] S5. The mixed resin system is subjected to vacuum degassing treatment at a vacuum degree of -0.08MPa for 10 minutes to obtain a carbon-titanium cage resin / epoxy resin composite matrix.

[0101] Comparative Example 6

[0102] This embodiment provides a coating material. Calculated by mass parts, the raw materials of the coating include 100 parts of carbon-titanium cage resin / polyurea resin composite matrix, 1.5 parts of KH-560 modified glass fiber, 0.25 parts of KH-560 modified graphene, 0.2 parts of defoamer (tributyl phosphate), and 0.5 parts of dispersant (BYK-110).

[0103] The preparation method of the carbon-titanium cage resin / polyurea resin composite matrix is ​​as follows:

[0104] S1. By mass, 40 parts of polyurea resin (Shenzhen Feiyang Junyan New Material Co., Ltd., F220) are added to a reaction vessel equipped with a mechanical stirrer, thermometer and cooling device, and stirred at 300 rpm for 20 min at 30℃.

[0105] S2. Under continuous stirring, 60 parts of 1020 carbon titanium cage resin (Shanghai Qixiang Qingchen) were slowly added to the polyurea resin at 500 r / min. After the addition was completed, stirring was continued for 30 min.

[0106] S3. Increase the stirring speed to 1000–1800 r / min for dispersion, and disperse for 20–40 min. High-speed shearing ensures that the carbon-titanium cage resin is uniformly dispersed in the polyurea resin.

[0107] S4. Then, 0.5 parts of dispersant (BYK-110) and 0.3 parts of defoamer (tributyl phosphate) were added to the above system and stirred at 500 r / min for 30 min to obtain a mixed resin system.

[0108] S5. The mixed resin system is subjected to vacuum degassing treatment at a vacuum degree of -0.08MPa for 10 minutes to obtain a carbon-titanium cage resin / polyurea resin composite matrix.

[0109] A coating material is applied to form a coating. The performance verification method for the coating is as follows:

[0110] 1. Adhesion

[0111] The test was conducted in accordance with GB / T 5210-2006 "Paints and Varnishes - Pull-off Adhesion Test". Pull-off test bars were attached to three different locations on the coating surface. A pull-off tester was used to apply a uniform load until the coating failed. The tensile stress at failure was recorded, and the arithmetic mean of the three tests was taken as the final result. The failure mode of the coating (interfacial failure, cohesive failure, and mixed failure) was also recorded.

[0112] 2. Impact resistance

[0113] The test shall be conducted in accordance with GB / T 1732-2020 "Determination of Impact Resistance of Paint Films". The impact tester shall be securely fixed, and the guide tube shall be perpendicular to the horizontal plane. Adjust the weight of the impact tester to a certain height using the weight controller. Place the test panel with the paint film facing upwards (positive impact) or downwards (reverse impact) on the base. The distance between the edges of the impact points on the test panel shall not be less than 10 mm, and the distance between the edges of adjacent impact points shall not be less than 10 mm. Press the control button of the weight controller, and the weight shall fall freely onto the impact head. Remove the test panel and observe whether there are cracks, wrinkles, or peeling of the paint film on the test panel. If no cracks, wrinkles, or peeling are observed, repeat the test at higher positions until cracks, wrinkles, or peeling are observed. Each increase in height shall be 5 cm or multiples of 5 cm. The result is expressed as the maximum height at which no cracks, wrinkles, or peeling are observed in three tests, expressed in kg·cm.

[0114] 3. Abrasion resistance

[0115] The test was conducted according to GB / T 1768-2006 "Determination of Abrasion Resistance of Paints and Varnishes - Rotary Rubber Grinding Wheel Method". The coated sample was cleaned with anhydrous ethanol, dried, and weighed initially to an accuracy of 0.1 mg. The sample was fixed, a rubber grinding wheel was installed, and pre-ground for 50 revolutions to remove burrs from the wheel surface. Test parameters were set as follows: load 500g, rotary wheel speed 60 r / min, total grinding revolutions 1000. After the test, abrasion debris was removed from the sample surface, cleaned with anhydrous ethanol, dried, and the post-test mass was weighed. The mass loss Δm was calculated as: initial mass - post-test mass. Each group of samples was tested in triplicate, and the arithmetic mean was taken as the final result.

[0116] 4. Corrosion resistance

[0117] The test was conducted according to GB / T 30648.1-2014 "Determination of resistance to liquids of paints and varnishes - Part 1: Immersion in liquids other than water". 5wt% HCl solution and 5wt% NaOH solution were used as the corrosive media. Two-thirds of the length of the coated test plate was immersed in these solutions at 23±2℃ for 168 hours. After immersion, the plate was cleaned and dried, and the surface condition of the coating was observed to check for blistering, discoloration, softening, chalking, etc. Corrosion resistance under both acidic and alkaline media was rated from 0 to 5.

[0118] Grade 0: No bubbling, no discoloration, no softening, no chalking, no peeling; Grade 1: Only slight loss of gloss or slight discoloration; Grade 2: Slight bubbling, slight softening or slight chalking, but no peeling; Grade 3: Obvious bubbling, obvious softening, obvious chalking, but no large-area peeling; Grade 4: Local peeling or local cracking; Grade 5: Large-area peeling, severe chalking, exposed substrate or complete failure.

[0119] 5. Salt spray resistance test

[0120] The test was conducted in accordance with GB / T 10125-2021 "Artificial Atmosphere Corrosion Test - Salt Spray Test". The sealed coating sample was placed in a salt spray test chamber and continuously sprayed with a 5% NaCl solution (pH 7). The temperature inside the chamber was controlled at 35±2℃ and the spray volume was controlled at 2mL / (h·80cm²). The sample was taken out for inspection every 240h. The surface salt spray deposits were rinsed off with running water and dried. The coating was then checked for rust, blistering, peeling and other phenomena. The longest salt spray exposure time that the coating could withstand before the first obvious failure was taken as the final salt spray resistance result.

[0121] The test results are shown in the table below.

[0122] Table 1 Test Results

[0123] Adhesion (MPa) Impact resistance (kg·cm) Abrasion resistance (mg) HCl corrosion resistance rating NaOH corrosion resistance rating Salt spray resistance (h) Example 1 8.5 55 32 0 0 2160 Example 2 7.8 48 38 0 0 1920 Example 3 8.8 60 31 0 0 2280 Example 4 8.1 52 35 0 0 2040 Comparative Example 1 6.9 40 49 1 1 1200 Comparative Example 2 7.4 42 45 1 1 1440 Comparative Example 3 7.6 45 41 1 1 1560 Comparative Example 4 5.8 31 65 2 2 720 Comparative Example 5 7.2 43 43 1 1 1320 Comparative Example 6 6.8 38 51 2 1 1080

[0124] The test results of Examples 1-4 show that, within the component and dosage range defined in this invention, the coatings exhibit good overall performance. Specifically, the mechanical properties and corrosion resistance of the coatings change with variations in the amounts of modified glass fiber and modified graphene, indicating that the amount of the two reinforcing components affects the internal reinforcing network and corrosive media barrier structure of the coating. When the dosage is within an appropriate range, good dispersion and interfacial bonding can be achieved, thereby resulting in superior overall coating performance.

[0125] When carbon-titanium cage resin is not added to the coating components and only vinyl ester resin is used as the matrix, its adhesion, corrosion resistance and salt spray resistance all decrease. This indicates that the composite matrix formed by carbon-titanium cage resin and vinyl ester resin can improve the structural stability of the coating and its barrier ability against corrosive media, and is an important component for improving the long-term protective performance of the coating.

[0126] When the coating component uses glass fiber that has not been treated with silane coupling agent, the interfacial bonding ability between the glass fiber and the resin matrix is ​​reduced. As a result, the coating is more prone to interfacial defects and cracks when subjected to impact or friction, which manifests as a decrease in impact resistance, abrasion resistance and long-term salt spray resistance. This indicates that modifying the glass fiber with silane coupling agent can effectively improve the interfacial bonding between it and the resin matrix.

[0127] When the coating component uses graphene without silane coupling agent treatment, its dispersion and interfacial bonding ability in the resin matrix are relatively weak, making it prone to local agglomeration or interfacial defects, which affects the barrier structure formed by the graphene. Therefore, compared with the examples, its acid and alkali corrosion resistance and salt spray resistance are reduced, indicating that silane coupling agent modification is beneficial to improving the dispersion stability and interfacial bonding ability of graphene in the resin matrix, thereby fully exerting its barrier and protective function.

[0128] Similarly, when the carbon-titanium cage resin is removed from the coating composition and unmodified glass fiber and graphene are used, the overall performance is significantly lower than in the example, indicating that it is difficult to simultaneously achieve good adhesion, impact resistance, abrasion resistance, and corrosion resistance by relying solely on ordinary resin matrix and unmodified reinforcing materials. This invention, through the synergistic effect of a composite resin matrix and two interface-modified reinforcing materials, allows each component to fully exert its function, thereby forming a multi-scale synergistic reinforcement and barrier protection effect.

[0129] Furthermore, Comparative Examples 5 and 6 show that, with other components remaining essentially the same, replacing vinyl ester resin with polyurea or epoxy resin resulted in lower overall performance compared to the embodiments of the present invention. This indicates that carbon-titanium cage resin does not necessarily achieve the same synergistic effect with different resins. Carbon-titanium cage resin and vinyl ester resin exhibit good compatibility in terms of interfacial bonding, film structure, and media resistance, and can co-construct a stable coating structure with modified glass fiber and modified graphene, thereby achieving superior overall protective performance.

[0130] In summary, this invention achieves a synergistic effect of resin matrix reinforcement, interface reinforcement, multi-scale mechanical reinforcement, and corrosive media barrier through the synergistic cooperation between the carbon-titanium cage resin / vinyl ester resin composite matrix, silane coupling agent modified glass fiber, and silane coupling agent modified dendritic porous graphene. This results in a coating with high adhesion, impact resistance, abrasion resistance, acid and alkali corrosion resistance, and salt spray resistance. It can reduce the intrusion of moisture, salt, and corrosive media into the metal substrate in the marine environment, and delay coating aging, cracking, and peeling, thereby improving the long-term protective capability of marine equipment.

[0131] This invention can also be implemented in various other ways. Without departing from the spirit and essence of this invention, those skilled in the art can make various corresponding changes and modifications according to this invention, but these corresponding changes and modifications should all fall within the protection scope of the appended claims.

Claims

1. An anti-aging and anti-corrosion coating material for marine equipment, characterized in that, The coating material comprises the following components in parts by weight: 100 parts of carbon-titanium cage resin / vinyl ester resin composite matrix; 1.0~2.5 parts of silane coupling agent modified glass fiber; 0.1-2.0 parts of graphene modified with silane coupling agent; Additives: 0.1-10 parts.

2. The coating material according to claim 1, characterized in that, The coating material comprises the following components in parts by weight: 100 parts of carbon-titanium cage resin / vinyl ester resin composite matrix; 1.0~1.6 parts of silane coupling agent modified glass fiber; 0.1~0.35 parts of graphene modified with silane coupling agent; Additives: 0.1-10 parts.

3. The coating material according to claim 1 or 2, characterized in that, The preparation method of the carbon-titanium cage modified vinyl ester resin includes the following steps: S1. Pretreatment of vinyl ester resin: Add vinyl ester resin to a reaction vessel equipped with a mechanical stirrer, thermometer and cooling device, and stir thoroughly until homogeneous; S2. Add carbon-titanium cage resin 1020: Under continuous stirring, slowly add carbon-titanium cage resin 1020 to vinyl ester resin; S3. High-speed dispersion: Increase the stirring speed to 1000-1800 r / min for dispersion, and the dispersion time is 20-40 min. S4. Adding additives: Add dispersant and defoamer to the above system to obtain a mixed resin system; S5. Vacuum degassing: The mixed resin system is subjected to vacuum degassing treatment to obtain a carbon-titanium cage resin / vinyl ester resin composite matrix.

4. The coating material according to claim 3, characterized in that, The ratio of carbon-titanium cage resin 1020, vinyl ester resin, dispersant, and defoamer, calculated by mass parts, is 50-70 parts: 30-50 parts: 0.1-0.5 parts: 0.05-0.3 parts.

5. The coating material according to claim 3, characterized in that, The vinyl ester resin is selected from one or more combinations of bisphenol A type epoxy vinyl ester resin, phenolic type epoxy vinyl ester resin, or polyurethane modified vinyl ester resin.

6. The coating material according to claim 1 or 2, characterized in that, The silane coupling agent is selected from one or a combination of two of KH-550 and / or KH-560.

7. The coating material according to claim 1 or 2, characterized in that, The glass fiber is chopped glass fiber.

8. The coating material according to claim 1 or 2, characterized in that, The preparation method of the silane coupling agent modified glass fiber includes the following steps: S1: After heating and drying the glass fiber, cool it to room temperature; S2: Mix silane coupling agent, water and ethanol to prepare a treatment solution, adjust the pH to 4-5 and stir; S3: The glass fiber treated in S1 is added to the above treatment solution for immersion. After immersion, it is filtered and dried to obtain silane coupling agent modified glass fiber.

9. The coating material according to claim 1 or 2, characterized in that, The preparation method of the silane coupling agent modified graphene includes the following steps: S1: Mix silane coupling agent, water and ethanol to prepare a treatment solution, adjust the pH to 4-5 and stir; S2: First, add graphene to ethanol and stir at low speed until homogeneous to obtain a graphene dispersion; S3: Add the graphene dispersion to the treatment solution and mix. Stir and treat. After treatment, centrifuge, wash and vacuum dry to obtain silane coupling agent modified graphene.

10. A method for preparing a coating material according to any one of claims 1 to 9, characterized in that, Includes the following steps: The silane coupling agent-modified graphene is added to the carbon-titanium cage resin / vinyl ester resin composite matrix and dispersed uniformly at high speed; then the silane coupling agent-modified glass fiber is added and stirred evenly; the additives are added further, and after mixing evenly, vacuum degassing is performed to obtain the anti-aging and anti-corrosion coating material for marine equipment.